Penggunaan Portal Rumah Belajar Sebagai Media Pembelajaran Bagi Guru SD di Kecamatan Ata Dei, Kabupaten Lembata, Nusa Tenggara Timur - Yosefina Helenora Jem; Stanislaus Guna; Yohanes Tresno Kurnianto (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
The demands of the 4.0 industrial revolution and the implementation of blended learning as the result of the COVID-19 pandemi are very solid in educational field. Teachers are required to be able to carry out distance learning activities by utilizing various learning media which are mostly technological-based. This Community Service aims at improving the ability and or skill of elementary school teachers in Ata Dei District, Lembata Regency in utilizing technological-based media in learning activities. 25 elementary school teachers in Ata Dei District involved in this PkM. The PkM was designed in two activities namely, seminar and workshop. The seminar was carried out for 3 hours while the workshop was carried out for 3 days. In this activity, a portal launched by KEMDIKBUD namely portal Rumah Belajar was introduced. It consists of 4 features, namely the sumber belajar feature, the laboratorium maya feature, the wahana jelajah angkasa feature and the edugame feature. The impact of this activity is increasing the knowledge and skills of elementary school teachers in Ata Dei District, Lembata Regency in using the portal rumah belajar as a digital technology-based learning media whic is effective and efficient in learning activities, especially daring learning.